Rekonstruksi Pemikiran Pendidikan Islam Tokoh Klasik dan Modern sebagai Landasan Pengembangan Pendidikan Islam di Indonesia - Irsyad Mahardi Harnandika; Ida Wahyu Erlina; Hidayat Hidayat; Mulyanto Abdullah Khoir (TSAQOFAH, 2026)
The development of Islamic education in Indonesia faces the challenges of social change, technological advancement, globalization, and the need to strengthen Islamic identity that is relevant to the contemporary context. This condition indicates the need to reconstruct Islamic educational thought rooted in the intellectual heritage of classical and modern figures as a basis for developing an adaptive and sustainable Islamic education system. This study aims to analyze, compare, and reconstruct the Islamic educational thought of classical and modern figures to formulate a conceptual framework for the development of Islamic education in Indonesia. This study employed a qualitative approach with a literature study or library research method. Data were obtained from primary literature in the form of works by classical and modern Islamic education figures as well as relevant secondary literature. The data were analyzed using content analysis, comparative analysis, and conceptual synthesis techniques. The results show that the thought of classical figures emphasizes the integration of knowledge, character formation, spiritual development, and a harmonious relationship between knowledge and practice. Meanwhile, the thought of modern figures emphasizes curriculum reform, the strengthening of critical thinking, the integration of religious knowledge and modern science, learning innovation, and responses to social change. The reconstruction of these two paradigms produces an integrative, transformative, humanistic, and contextual model of Islamic education as a foundation for the development of Islamic education in Indonesia. The conclusion of this study emphasizes the importance of integrating classical and modern values in building a paradigm of Islamic education that is responsive to the challenges of the 21st century. The implications of the study include theoretical contributions to strengthening the paradigm of Islamic education and practical implications for curriculum development, improving educator competence, learning innovation, and formulating adaptive and sustainable Islamic education policies.